LINGUISTIC AND CULTURAL FEATURES OF LACUNAR UNITS - Bakhodir Suyunov; Ulmas Saidov; Kholida Gulyamova; Shakhnoza Mukhtarova (The Bioscan, 2024)
This article reflects the lacunar units in Uzbek language and their linguocultural features. A number of foreign literature and scientific and theoretical sources on this topic are analyzed. In particular, the absence of a lexical unit or word of one language in another language, as well as the impossibility of expressing a word in another language due to the lack of an equivalent unit for the same word, the expression of such units, as a rule, through interpretation or description or through nonequivalent words - are studied within the framework of the concept of lacuna. The author divides the socio-cultural lacunae of our life into such types as subjective, communicative, cultural lacunae and textual lacunae, explains their national-cultural features, various national-cultural discrepancies in communicative activity and communication, as well as some specific communicative situations in a broad sense. In the analyzed lacunae units, national-cultural and linguacultural traditions and specificity of Uzbek people and other peoples are revealed.